0.013 mm2 and Low‐power 10 Gb/s Transimpedance Amplifier for Short‐reach Optical Interconnects. Issue 10 (26th July 2013) - Nguyen, Nga T. H.; Ukaegbu, Ikechi Augustine; Sangirov, Jamshid; Cho, Mu Hee; Lee, Tae Woo; Park, Hyo Hoon
ABSTRACT A transimpedance amplifier (TIA) has been designed and implemented for short‐reach optical interconnect applications. The TIA, which is based on the regulated cascode technique, is implemented with a bandwidth enhancement technique, where capacitive degeneration and resistive feedback has been exploited in a 0.13 μm CMOS technology, while maintaining a small chip area and low power consumption. The TIA showed a measured transimpedance gain of 51dBΩ and works up to 10 Gb/s in the presence of 0.3 pF input photodiode capacitance. It occupies an active area of 0.013 mm2 with a power dissipation of 4.3 mW. The proposed TIA achieved high gain‐bandwidth product per DC power (GBP/DC) figure of merit of 589 GHzΩ/mW with an input referred noise of 20 pA/√Hz. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:2484–2487, 2013